Spiritualitas sebagai Mekanisme Koping Perempuan Pasca Kematian Orang Tua akibat Covid-19: Studi Kasus Perspektif Tasawuf - Harjuna, Rafiq Tri Belan; Gusman, Gusman (JENTRE, 2025)
This study aims to explore the role of spirituality in facilitating psychological adjustment and coping among women who lost their parents due to the Covid-19 pandemic. Employing a qualitative approach with a case study method, the research involved three female participants aged 20–40 who experienced the loss of one or both parents during the pandemic. Data were collected through in-depth interviews and analyzed using thematic coding. The findings reveal that spirituality significantly contributes to psychological resilience by fostering inner connection, social awareness, and transcendental experiences. From a Sufi perspective, the participants' experiences reflect spiritual stages (maqāmāt), such as patience (ṣabr), acceptance (riḍā), and trust in God (tawakkul), which enhanced their emotional stability and helped them cope with grief. The study concludes that spirituality—both theistic and non-theistic—functions as an adaptive coping mechanism, promoting psychological recovery and resilience. It is recommended that grief-support interventions integrate spiritual approaches, particularly in culturally and religiously diverse contexts, to support emotional healing after trauma.